Fear Of Missing Out pada Pengguna Media Sosial dan Kaitannya dengan Loneliness Di Masa Pandemi Covid-19 - Salinding, Jessica Medly; Soetjiningsih, Christiana Hari (Psikoborneo: Jurnal Ilmiah Psikologi, 2022)
During the pandemic, social media has a big influence on students, causing feelings of loneliness and fear of missing out. Individuals who experience loneliness need closeness with other individuals, but this is not obtained by the individual, resulting in a feeling of fear of missing out. This study is aims to determine the correlation between loneliness and fear of missing out on Satya Wacana Christian University Psychology Faculty students during the pandemic. In this study, the loneliness measured by the UCLA loneliness scale (Version 3), while the fear of missing out by fear of missing out scale. Participants in this study were students of the Faculty of Psychology, class of 2018-2020, the participants in this study were 161 students. From the results of hypothesis test was analyzed by Pearson correlation product moment shows that there is a correlation between loneliness and fear of missing out with a correlation coefficient of 0.298 and significance value of 0.000 (p<0.05). This means that if the higher the level of loneliness, the higher the level of fear of missing out in students. Di masa pandemi, media sosial sangat berpengaruh besar terhadap mahasiswa hingga menimbulkan perasaan loneliness dan fear of missing out. Individu yang mengalami loneliness membutuhkan closeness dengan individu lain, namun hal ini tidak didapatkan oleh individu tersebut, sehingga timbul perasaan fear of missing out. Tujuan penelitian ini untuk mengetahui hubungan antara loneliness dan fear of missing out pada mahasiswa Fakultas Psikologi Universitas Kristen Satya Wacana pada masa pandemi. Dalam penelitian ini, variabel loneliness diukur menggunakan UCLA loneliness Scale (Version 3), sedangkan untuk fear of missing out menggunakan fear of missing out scale. Partisipan dalam penelitian ini adalah mahasiswa Fakultas Psikologi angkatan 2018-2020 yang berjumlah 161 mahasiswa. Dari hasil uji hipotesis yang dilakukan dengan teknik Pearson correlation product moment dan menunjukkan hasil bahwa terdapat hubungan positif antara loneliness dan fear of missing out dengan kofisien korelasi kedua variabel sebesar 0,289 dan nilai signifikansi sebesar 0,000 (p<0,05). Artinya bahwa semakin tinggi tingkat loneliness maka akan tinggi pula tingkat fear of missing out.